Long-term cancer risk in users of GLP-1 agonists in Denmark: a nationwide emulated trialResearch in context - Mads Gamborg; Mia Klinten Grand; Kathrine Grell; Susanne Rosthøj; Ulrik Pedersen-Bjergaard; Christian Torp-Pedersen; Lina Steinrud Mørch (The Lancet Regional Health. Europe)
Summary: Background: The long-term cancer safety of glucagon-like peptide-1 receptor agonists (GLP-1RAs) in real-world settings remains unclear, with limited long-term clinical and observational studies. We clarify the long-term cancer risk. Methods: This register-based nationwide emulated trial includes all Danes initiating treatment with GLP-1RA or dipeptidyl peptidase-4 inhibitors (DPP-4i) 2007–2019, propensity score matched 1:1 on baseline characteristics and followed 10 years. The primary outcome was risk differences for cancer, estimated for long-term sustained use of GLP-1RA vs DPP-4i using g-computation accounting for time-varying patient characteristics. Secondary outcomes included “death without prior cancer” and the composite outcome “death or cancer”. Analyses included sex stratified estimates and Cox hazard ratios (HR). Findings: After 195,702 person-years 4758 developed cancer. Among sustained users of GLP-1RA, 4·1 (95% CI 0·4–7·2) more patients developed cancer per 100, compared to 100 DPP-4i patients 10-years post-initiation (HR: 1·35 [95% CI 1·05–1·73] 6–10 years post-initiation). The excess cancer risk was 6·6 (95% CI 1·8–10·7) per 100 women and 2·2 (95% CI −2·2 to 6·2) per 100 men. Fewer patients “died without prior cancer” in users of GLP-1RA (per 100 users: −4·9 [95% CI −7·6 to −2·4]). There was no difference in risk of “death or cancer” per 100 users: −1·15 (95% CI −4·9 to 2·5). Interpretation: Long-term sustained users of GLP-1RA had a small increased risk of cancer; potentially explained by a survival benefit. Residual confounding by body mass index cannot be ruled out. Funding: The Scientific Committee of the Danish Cancer Society (R354-A20492-23-S3 to LSM).